Screening for feeding difficulties in the neonatal unit: Sensitivity and specificity of gestational age vs. medical history. Issue 3 (June 2019) - Edney, Sarah K.; Jones, Stephanie; Boaden, Elizabeth
Abstract: Background: Studies to inform feeding interventions on neonatal units are lacking. This study aims to compare gestational age and medical history as methods of identifying infants at higher risk of developing feeding difficulties by 40 weeks gestational age. Method: A retrospective case note analysis was conducted on a level 3 neonatal unit. Infants were given a severity category based on gestational age at birth and medical history. Feeding outcomes were analysed for sensitivity, specificity, and positive and negative predictive values. Results: 233 infants were included. Medical history at severity level 2 provided a high level of sensitivity (84.62%) and specificity (87.92%) for feeding difficulties at 40 weeks gestational age. Conclusion: Medical history can be used as a simple method to identify infants at highest risk of feeding difficulties prior to commencing oral feeding, enabling the targeting of preventative therapeutic interventions and caseload prioritisation.